2006
DOI: 10.1111/j.1749-4486.2006.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

How we do it: Patient participation in cochlear implant selection

Abstract: . Involving patients and parents in the choice of their cochlear implant encourages an active role in the process and facilitates 'bonding' and 'ownership' of the device. . The most frequent reasons given by patients for selecting a device included cochlear implant comfort and appearance. . We describe the Implant Programme based at the Royal National Throat, Nose and Ear Hospital, London, and also examine patient satisfaction with the scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…In the current service evaluation, the most common reason reported by the patients and the parents of the children was related to comfort and fit, looks, and size of the processor. The results were similar to the audit done by Geyer et al (2006) using the previous generation of implants and processors. The authors concluded that the most common reasons are related to the cosmetic appearance and comfort which is similar to our service evaluation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the current service evaluation, the most common reason reported by the patients and the parents of the children was related to comfort and fit, looks, and size of the processor. The results were similar to the audit done by Geyer et al (2006) using the previous generation of implants and processors. The authors concluded that the most common reasons are related to the cosmetic appearance and comfort which is similar to our service evaluation.…”
Section: Discussionsupporting
confidence: 80%
“…As a centre we do not prefer one supplier above another while their device is on the market. Geyer et al (2006) studied the reasons for choosing a particular device on the older generation of devices and found that the main factor was aesthetics. The current paper describes the reasons reported by patients and parents for choosing a particular device with the latest generation of implants and processors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings in Japan & South East Asia (Okubo, Takahashi, and Kai 2008;Chundu and Stephens 2013) particularly highlighted concerns about costs. Work on shared decision making in CI has focussed on type of implant (Geyer et al 2006;Clamp et al 2013). Little is known about the decision made by the eligible patient on whether or not they pursue CI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adults and children reported higher satisfaction and usability with several aspects of the Neuro 2, compared to the Neuro One: size and appearance, wearing comfort, clarity of instructions, battery lifetime, options (rechargeable and single-use), and changing ease, antenna retention, and robustness of the sound processor and accessories. This shows how both adult users and parents of paediatric users highly value the appearance, wearing comfort, and robustness of cochlear implant sound processors (Chundu and Stephens 2013;Clamp et al 2013;Geyer et al 2006).…”
Section: Self-reported Listening Ability Satisfaction and Usabilitymentioning
confidence: 93%
“…Neuro 2 introduces improved design with smaller size and lighter weight as well as new powering options such as rechargeable batteries. Several studies have shown that visual appearance, wearing comfort on the ear, and robustness/reliability were key drivers for cochlear implant choices for both adults and parents of children (Chundu and Stephens 2013;Clamp et al 2013;Geyer et al 2006).…”
Section: Neuro 2 Sound Processormentioning
confidence: 99%